A new fossil Tanytarsus from Eocene Baltic amber, with notes on systematics of the genus (Diptera: Chironomidae) - Giłka, Wojciech (Zootaxa, 2011)
Tanytarsus fereci sp. nov. is described from a specimen found in Eocene Baltic amber. The new species is compared with the fossil Tanytarsus serafini Giłka and with the extant T. aculeatus Brundin. Following the analysis of morphological diagnostic characters, T. fereci is placed in the mendax species group.